Transaction Costs in Resource Redeployment for Multiniche Firms - Giarratana, Marco S.; Santaló, Juan (Organization Science, 2020)
Transaction costs strongly influence diversification dynamics, as predicted by resource theory. A mainstream view links the profitability of diversification with the existence of transaction costs that prevent a firm from trading in fungible, scale-free resources. This study applies a neo-Penrosian perspective to transaction costs, with the notion that diversification may be driven by the redeployment of non-scale-free resources. An empirical analysis, using tax changes in the drink sector as a measure of exogenous demand variation, offers results consistent with the prediction that redeployment is particularly relevant when retailing is concentrated and single-product competition within a focal product niche (e.g., beer) is fragmented. This study also measures redeployment across a portfolio of a multiniche firm when changes in its sales-growth rates for a particular product niche might imply contrasting changes in other product niches. The resulting evidence is consistent with predictions that demand uncertainty, and transaction costs create viable redeployment opportunities for multiniche companies.